STEAM EDUCATION AS A BENCHMARK FOR INNOVATIVE TRAINING OF FUTURE TEACHERS OF LABOUR TRAINING AND TECHNOLOGY - Hlukhaniuk, Vitalii; Solovei, Viktor; Tsvilyk, Svitlana; Shymkova, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the article is to substantiate an innovative methodology for implementing the content of STEAM (science, technology, engineering, arts and math) education through the organization of creative projects of future teachers of labour training and technology.The future teacher should be able to fulfil the tasks of integration of different subject areas, to use knowledge from different disciplines to describe the system of transformative activity; to make well-founded structural and technological decisions and put them into practice; to choose rational ways, to plan, predict and evaluate efficiency of transformative activity; to create spatial models of products or processes.Investigating this problem, we used the methods of research: analysis and synthesis to clarify the basic concepts and categories of STEAM education; conceptual analysis for comparing traditional and STEAM-oriented approaches, curricula and programs, psychological-pedagogical and scientific-methodical literature, materials of scientific-practical conferences on the problem of research, advanced innovative pedagogical experience.The organization of project activities contributes to the formation of sustainable motivation in teaching the disciplines on which STEAM education is based. Creating a product from conception to implementation, students are aware of the integral theoretical and practical importance of knowledge in the natural-mathematical and technical disciplines of cycles of general and vocational training.